2023
DOI: 10.1002/smsc.202300002
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Imaging of the Mechanobactericidal Action of Colloidal Nanomaterials and Nanostructured Topographies

Abstract: Mechanobactericidal nanomaterials, such as low‐dimensional nanoparticles in suspension or high‐aspect‐ratio nanofabricated topographies, rely on their mechanical or physical interactions with bacteria and are promising antimicrobial strategies that overcome bacterial resistance to classical antibiotics. However, the underlying killing mechanisms are poorly understood, given the challenges associated with the real‐time characterization of the mechanical interaction in a biologically relevant environment. Indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…During that irradiation period, 4 min movies were acquired at the start and before the end of irradiation. After the 660 nm LED was turned off, bacteria were left in the dark for 6 min and a final movie was acquired postirradiation, since we have previously shown that it can take up to 10–20 min for the activation of stress responses or metabolic changes that lead to an observable change in the oscillation period Figure shows representative behavior for a bacterium in an irreversibly loaded hydrogel during the imaging steps described above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During that irradiation period, 4 min movies were acquired at the start and before the end of irradiation. After the 660 nm LED was turned off, bacteria were left in the dark for 6 min and a final movie was acquired postirradiation, since we have previously shown that it can take up to 10–20 min for the activation of stress responses or metabolic changes that lead to an observable change in the oscillation period Figure shows representative behavior for a bacterium in an irreversibly loaded hydrogel during the imaging steps described above.…”
Section: Resultsmentioning
confidence: 99%
“…After the 660 nm LED was turned off, bacteria were left in the dark for 6 min and a final movie was acquired postirradiation, since we have previously shown that it can take up to 10−20 min for the activation of stress responses or metabolic changes that lead to an observable change in the oscillation period. 25 Figure 4 shows representative behavior for a bacterium in an irreversibly loaded hydrogel during the imaging steps described above. It can be clearly seen that the oscillation period increases immediately after MB irradiation and becomes even slower as the experiment progresses.…”
Section: Real-time Single Bacterial Imaging In Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study has investigated how Min oscillations in E. coli respond to weak mechanical perturbations in a more realistic scenario of interactions between bacteria and mechano-bactericidal nanomaterials [ 48 ]. To that end, nanostructured topographies and ‘nanodarts’, exemplified by flowing SWCNTs, were used to inflict a physiological response on bacteria.…”
Section: Min Oscillations As Reporter Of Environmental Challengesmentioning
confidence: 99%
“…These advantages are similar to those provided by fluorescence lifetime imaging from the quantitative point of view, namely an independence of heterogeneities in the sample and imaging system, as well as in the fluorophore concentration [ 65 ]. This is particularly interesting for experiments in microfluidic systems or on non-uniform surfaces such as nanofabricated topographies mentioned above [ 48 ].…”
Section: Oscillations As a Reporting Tool In Fluorescence Microscopymentioning
confidence: 99%